A review of thermoelectric power generation systems: Roles of existing test rigs/ prototypes and their associated cooling units on output performance - Alghoul M.A.; Shahahmadi S.A.; Yeganeh B.; Asim N.; Elbreki A.M.; Sopian K.; Tiong S.K.; Amin N. (Elsevier Ltd, 2023)
Cooling; Thermoelectric equipment; Thermoelectric power; Thermoelectricity; Waste heat; Waste heat utilization; Active cooling; Contact pressures; Cooling methods; Output performance; Output power; Research studies; Test rigs; Thermo-electric modules; Cooling systems